Aboriginal Populations: Social Demographic and Epidemiological Perspectives - Don Kerr (University of Western Ontario, 2015)
This edited collection provides a valuable overview of Aboriginal demography, with a primary yet not exclusive emphasis upon Canadian research. It provides the reader with much insight not only into the major demographic, sociological, and health trends to characterize Aboriginal peoples, but also some of the most serious conceptual and methodological issues that hinder research of this nature. With additional contributions from the United States, Australia, New Zealand, as well as the circumpolar northern regions of Greenland, Norway, Sweden, Finland, and Russia, this book also addresses how Aboriginal conditions in these countries may resemble or differ from those in Canada. For this reason, this edited collection is valuable to those who are interested in using demographic, socioeconomic, and epidemiological data as a basis for guiding policy, both in Canada and internationally. The contributions are by and large non-technical in nature and, for this reason, accessible to a wide readership.